Magnetic resonance imaging of the lentiform nuclei in dogs with portosystemic shunts. (12th February 2015) - Mortera‐Balsa, V.; Penderis, J.; Wessmann, A.; Gonçalves, R.; Lowrie, M.; Gutierrez‐Quintana, R.
<x xml:space="preserve">Abstract</x> OBJECTIVES To develop and evaluate a method to quantify the T1‐weighted magnetic resonance imaging signal intensity of the lentiform nuclei in dogs, and to determine if there is any significant difference in this signal intensity between dogs with portosystemic shunts and a control group. MATERIALS AND METHODS A retrospective blinded study was performed to investigate the reliability and use of a quantitative method for assessing the T1‐weighted magnetic resonance imaging signal intensity of the lentiform nuclei in dogs with and without portosystemic shunts. The lentiform nuclei index (mean lentiform nucleus signal intensity/mean white matter signal intensity) was calculated for nine dogs with portosystemic shunts and a control group of 14 dogs. RESULTS The intra‐ and inter‐observer intraclass correlation coefficients were considered excellent (>0 · 75), suggesting that the lentiform nuclei index is a reliable method. The dogs with portosystemic shunts had a higher lentiform nuclei index than the control group (P = 0 · 0127). CLINICAL SIGNIFICANCE This method of quantifying the T1‐weighted magnetic resonance imaging signal intensity of the lentiform nuclei was reliable and showed that dogs with portosystemic shunts tend to have increased signal intensity. Further prospective studies are necessary to investigate the clinical significance and applications of these findings.